PENDEKATAN HERMENEUTIKA DALAM STUDI NASKAH TAFSIR AL-QUR'AN - khairul rahmad, khairul; Misnawati (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
The sacred text known as the Qur'an has been, continues to be, and will continue to be interpreted across time. As science and time have advanced, hermeneutical techniques or procedures have started to emerge as substitute tools for illuminating the meaning of a verse's text. A form of interpretation known as hermeneutics looks at the verse's language as well as its literal meaning if possible. Therefore, it is envisaged that the Hermeneutics approach will be able to uncover aspects that are not known by traditional interpretation techniques. Examining the hermeneutical approach to the study of the Al-Qur'an manuscript is the goal of this article. The type of research used in this research is library research. When accepting a method that is relatively new, Muslims must be able to act wisely, not reject it blindly and also not accept it completely. A selective attitude is very necessary. Accepting hermeneutics as an interpretive method aims to understand the nuanced world of texts from the past with the current empirical world. This aims to bring the two of them closer together so that they can answer all the problems that occur in society. Of course, while still paying attention to the rules of interpretation that have been formulated by scholars.